Anti-fatigue phosphogypsum recycled aggregate water-stable base material and preparation method thereof
By using composite polymer emulsions and solid alkali exciters in road base materials to form film-forming structures, the problem of poor fatigue performance of existing materials is solved, and higher compressive strength, water loss resistance and fatigue resistance are achieved.
Patent Information
- Application Number
- CN202411839688.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The fatigue performance of existing road base materials is poor under repeated stress, resulting in material cracking and reduced durability.
The composite polymer emulsion (a mixture of EVA emulsion, SBR emulsion and PU emulsion) and solid alkali exciter are used to penetrate into the internal pore structure of the base material to form films to improve stiffness and compressive strength, while improving the elastic deformation ability and fatigue resistance of the material.
It significantly improves the compressive strength, water loss resistance and fatigue resistance of road base materials, and extends the service life of the material.
Smart Images

Figure BDA0005187661860000231 
Figure BDA0005187661860000241 
Figure BDA0005187661860000251
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to an anti-fatigue phosphogypsum recycled aggregate water-stable base material and a preparation method thereof. Background Art
[0002] Phosphogypsum is a solid waste produced in the wet phosphoric acid process, and its main component is calcium sulfate dihydrate. With the acceleration of industrialization and urban modernization, the demand for phosphoric acid in social development has increased year by year. However, for every ton of phosphoric acid produced, 5 tons of phosphogypsum will be produced, which leads to a large accumulation of solid waste materials such as phosphogypsum. At present, the treatment of phosphogypsum is often carried out in the form of open-air stacking. Phosphogypsum also contains a small amount of harmful substances, such as fluoride, phosphorus pentoxide and a small amount of radioactive elements, which will pollute nearby rivers, land and groundwater resources with rainwater. Therefore, the use of solid waste materials such as phosphogypsum in road materials can not only play an environmental protection role, but also create the economic value of phosphogypsum.
[0003] The main purpose of the fatigue test of road base materials is to evaluate the fatigue life and fatigue strength of the material under repeated stress, which can provide an important basis for the design of the pavement structure and ensure the safety and reliability of the pavement. Phosphogypsum is a powder material, similar to the powdery minerals in road materials. Prior art such as application number 202211536774.7 discloses a method for preparing a phosphogypsum recycled aggregate road base material, through the stabilization of phosphogypsum and recycled aggregate by organic-inorganic gelling materials, and the synergistic stabilization of the mixture of pavement base materials by organic gelling materials, which can reduce the rigidity of the pavement base stabilized by inorganic gelling materials to a certain extent, reduce the probability of cracking of the base material due to thermal shrinkage stress and load stress, and significantly improve the durability such as anti-freeze-thaw cracking, and add an appropriate amount of styrene-butadiene emulsion water-resistant reinforcing material to optimize the crack resistance and water resistance of the phosphogypsum recycled aggregate road base material. However, the fatigue performance of the above-mentioned organic-inorganic gelling materials synergistically stabilized phosphogypsum road base materials is poor. Summary of the invention
[0004] The purpose of the present invention is to provide a fatigue-resistant phosphogypsum recycled aggregate water-stable base material and a preparation method thereof, in order to solve the cracking problem caused by shrinkage and temperature shrinkage of existing road base materials. The composite polymer emulsion is used. On the one hand, the infiltration can optimize the internal pore structure of the road base material, and it can form a film in the base material, which can strengthen the rigidity of the base material system, improve the compressive strength of the base material, and improve the water damage resistance of the road base material; on the other hand, due to the effects of semi-rigidity and elasticity, while forming a film, the overall elastic deformation capacity of the base material is improved, thereby improving the deformation characteristics of the road base material, improving the fatigue resistance of the road base material, and stabilizing the compressive strength and other mechanical properties of the phosphogypsum recycled aggregate water-stable base material.
[0005] In order to achieve the above purpose, the technical solution adopted in this application is:
[0006] The first object of the present invention is to provide an anti-fatigue phosphogypsum recycled aggregate water-stable base material, which is prepared from a solidifying combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the solidifying combination, the solid alkali activator, the composite polymer emulsion and water is 100:1-3:2-6:5-8, and the solidifying combination is composed of the following raw materials in mass percentage: 4%-6% of cement-based materials, 17%-22% of phosphogypsum, 28%-31% of recycled fine aggregate, and 44%-48% of recycled coarse aggregate, which is 100% in total; the composite polymer emulsion is obtained by mixing EVA emulsion, SBR emulsion and PU emulsion according to a mass ratio of 0.1-1.6:1-4.5:0.8-3.2.
[0007] Furthermore, the composite polymer emulsion is obtained by mixing EVA emulsion, SBR emulsion and PU emulsion in a mass ratio of 0.2-1.6:1-2:0.8-3.2.
[0008] Furthermore, the mass ratio of the solidified combination to the composite polymer latex is 100:2.2-3.5.
[0009] Furthermore, the solid base activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 1:3.2 to 8.8.
[0010] Furthermore, the cement-based material is cement or a mixture of cement and mineral admixtures, wherein the mineral admixture is at least one of waste steel slag, fly ash, slag, and stone powder.
[0011] Furthermore, the recycled fine aggregate is obtained by crushing and screening waste concrete materials; the particle size is 0.075 mm to 4.75 mm, and the continuous grading method is adopted, and the apparent density is 1960 kg / m 3 ~2100kg / m 3The water absorption rate is 4% to 8%, and the moisture content is 2% to 5%.
[0012] Furthermore, the recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence; the particle size is 4.75 mm to 19 mm, and the apparent density is 1980 kg / m 3 ~2180kg / m 3 The crushing index is 10% to 17%, the water absorption rate is 4% to 11%, and the moisture content is 4% to 7%.
[0013] Furthermore, the particle size of the phosphogypsum is distributed below 0.3 mm, and the phosphogypsum is dried during use, with a drying temperature of 100° C. to 104° C. and a drying time of 20 h to 28 h.
[0014] Furthermore, the EVA emulsion has a solid content of 35% to 55% and a pH value of 6.0 to 7.0; the SBR emulsion has a solid content of 35% to 55% and a pH value of 7.0 to 8.0; and the PU emulsion has a solid content of 35% to 55% and a pH value of 7.0 to 9.0.
[0015] The second object of the present invention is to provide a method for preparing the above fatigue-resistant phosphogypsum recycled aggregate water-stable base material, comprising the following steps:
[0016] Weigh each component according to mass percentage.
[0017] The recycled coarse aggregate and the recycled fine aggregate are mixed evenly to form a mixture A; the composite polymer emulsion and water are mixed evenly to form a mixture B; the cement-based material, the solid alkali activator and the phosphogypsum are mixed evenly to form a mixture C.
[0018] Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stabilized base material.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The composite polymer emulsion provided by the present invention is a mixture of EVA emulsion, SBR emulsion and PU emulsion. The composite polymer emulsion has multiple properties such as rigidity, semi-rigidity and elasticity. On the one hand, the infiltration can optimize the internal pore structure of the road base material, and it can form a film in the base material, which can strengthen the rigidity of the base material system, improve the compressive strength of the base material, and also improve the water damage resistance of the road base material; on the other hand, due to the effects of semi-rigidity and elasticity, while playing a film-forming role, it improves the overall elastic deformation capacity of the base material, thereby improving the deformation characteristics of the road base material, improving the fatigue resistance of the road base material, and stabilizing the mechanical properties of the road base material such as the compressive strength.
[0021] (2) NaOH is added to the solid alkali activator used in the present invention. Since the pH value of solid waste phosphogypsum is acidic, the pH value is 5.2-6.4 in a naturally humid state. Therefore, the NaOH added to the solid alkali activator can adjust the pH value of the road base material to make the pH value alkaline, and at the same time release a large amount of heat to provide a good environment for the hydration reaction. The solid alkali activator contains sodium silicate. After the road base material is mixed with water, the sodium silicate meets sodium hydroxide and a chemical reaction occurs to generate silicate colloid. The silicate colloid reacts with water to form hydrated silicate. In this process, the interaction between the silicate colloid and water causes the silicate colloid to absorb water and swell, and finally forms a hydrated silicate gel. Under appropriate conditions, the silicate colloid can further polymerize to form a three-dimensional network structure, which has good adhesion and stability. It can better improve the compressive strength of the road base material.
[0022] (3) The present invention adopts a full solid waste aggregate system. It fully develops the potential value of large-scale utilization of waste concrete in road bases and saves natural aggregate resources. At the same time, the characteristics of the lower elastic modulus of recycled aggregates compared to traditional aggregates are utilized. Under the same load, the deformation performance of recycled aggregates is stronger than that of traditional aggregates, thereby improving the deformation characteristics of road base materials and improving the fatigue resistance of road base materials; the phosphogypsum material used is ordinary solid waste phosphogypsum, which is only dried before use. Compared with other pretreatment methods for phosphogypsum, such as water washing, calcination, grinding modification and other methods, this method of use is more convenient, the cost is greatly reduced, and it is convenient for large-scale industrial production. It can realize the recycling of solid wastes such as phosphogypsum and waste concrete materials, and effectively ensure that the prepared water-stable base materials have excellent fatigue resistance, which has important economic and promotion value. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0025] Prior art, such as application number 202211536774.7, discloses a method for preparing a phosphogypsum recycled aggregate road base material. Through the stabilization of phosphogypsum and recycled aggregate by organic-inorganic gelling materials, the mixture of road base materials is synergistically stabilized by organic gelling materials, which can reduce the rigidity of the road base stabilized by inorganic gelling materials to a certain extent, reduce the probability of cracking of the base material due to thermal shrinkage stress and load stress, and significantly improve the durability of anti-freeze-thaw cracking, and add a proper amount of styrene-butadiene emulsion water-resistant reinforcing material to optimize the crack resistance and water resistance of the phosphogypsum recycled aggregate road base material. However, the fatigue performance of the above-mentioned organic-inorganic gelling materials synergistically stabilized phosphogypsum road base material is poor.
[0026] Based on the above problems, on the one hand, the present invention provides an anti-fatigue phosphogypsum recycled aggregate water-stabilized base material, the water-stabilized base material is prepared from a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:1-3:2-6:5-8, and the consolidation combination is composed of the following raw materials in mass percentage: 4%-6% cement-based material, 17%-22% phosphogypsum, 28%-31% recycled fine aggregate, 44%-48% recycled coarse aggregate, totaling 100%; the composite polymer emulsion is obtained by mixing EVA emulsion, SBR emulsion and PU emulsion in a mass ratio of 0.10-1.6:1-5.5:0.8-3.2.
[0027] The composite polymer emulsion provided by the present invention is a mixture of EVA emulsion, SBR emulsion and PU emulsion. The composite polymer emulsion has multiple properties such as rigidity, semi-rigidity and elasticity. On the one hand, the infiltration can optimize the internal pore structure of the road base material, and it can form a film in the base material, which can strengthen the rigidity of the base material system, improve the compressive strength of the base material, and also improve the water damage resistance of the road base material; on the other hand, due to the effects of semi-rigidity and elasticity, while playing a film-forming role, the overall elastic deformation capacity of the base material is improved, thereby improving the deformation characteristics of the road base material, improving the fatigue resistance of the road base material, and stabilizing the mechanical properties of phosphogypsum and the road base material such as the compressive strength.
[0028] The present invention adopts a solid alkali activator to react with water to form a silicate colloid, and the interaction with water causes the silicate colloid to absorb water and swell, and finally form a hydrated silicate gel, thereby forming a three-dimensional network structure in the base material, which has better adhesion and stability, and can better improve the compressive strength of the road base material.
[0029] The present invention adopts a full solid waste aggregate system. It fully develops the potential value of large-scale utilization of waste concrete in road base, and saves natural aggregate resources. At the same time, it utilizes the characteristics of low elastic modulus of recycled aggregate compared with traditional aggregate. Under the same load, the recycled aggregate has stronger deformation performance than traditional aggregate, thereby improving the deformation characteristics of road base materials and improving the fatigue resistance of road base materials.
[0030] In some embodiments, the composite polymer emulsion is obtained by mixing EVA emulsion, SBR emulsion and PU emulsion in a mass ratio of 0.2 to 1.6: 1 to 4.5: 0.8 to 3.2. In the present invention, the polymer molecules in EVA emulsion, SBR emulsion and PU emulsion are mutually entangled and physically adsorbed to form a stable blending system. In the road base material system, EVA emulsion is vinyl acetate-ethylene copolymer emulsion with a solid content of 35% to 55% and a pH value of 6.0 to 7.0. It has good flexibility and low temperature performance, and has high hydrophilicity. It also acts as a dispersant and plasticizer for SBR emulsion and PU emulsion to improve the overall elastic deformation capacity of the base material; SBR emulsion is styrene-butadiene rubber emulsion with a solid content of 35% to 55%. 5%, pH value is 7.0-8.0, which can improve the toughness, elasticity and wear resistance of the blended system, and make the film layer after film formation more firm and durable; PU emulsion is a polyurethane emulsion with a solid content of 35%-55% and a pH value of 7.0-9.0. It is a buffer material with excellent properties such as elasticity, adhesion, flexibility, impact resistance and reduced brittleness. Its penetration can optimize the internal pore structure of the road base material, and at the same time play a film-forming role, thereby improving the water damage resistance of the road base material. At the same time, it can strengthen the rigidity of the base material system and improve the compressive strength of the base material.
[0031] In some embodiments, the mass ratio of the solidified combination to the composite polymer latex is 100:2.2-3.5.
[0032] In some embodiments, the solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 1:3.2 to 8.8. NaOH (sodium hydroxide) is added to the solid alkali activator used in the present invention. Since the pH value of solid waste phosphogypsum is acidic, the pH value is 5.2 to 6.4 in a naturally humid state. Therefore, the NaOH added to the solid alkali activator can adjust the pH value of the road base material to make the pH value alkaline, while releasing a large amount of heat to provide a good environment for the hydration reaction. The solid alkali activator contains sodium silicate. After the road base material is mixed with water, sodium silicate and sodium hydroxide meet, a chemical reaction will occur, and silicate colloid will be generated. The silicate colloid reacts with water to form a hydrated silicate. In this process, the interaction between the silicate colloid and water causes the silicate colloid to absorb water and swell, and finally forms a hydrated silicate gel.
[0033] In some embodiments, the cement-based material is cement or a mixture of cement and mineral admixtures, wherein the mineral admixture is at least one of waste steel slag, fly ash, slag, and stone powder.
[0034] In some embodiments, the recycled fine aggregate is obtained by crushing and screening waste concrete materials; the particle size is 0.075 mm to 4.75 mm, and it is mixed in a continuous grading manner, and the apparent density is 1960 kg / m 3 ~2100kg / m 3 , water absorption rate is 4% to 8%, and moisture content is 2% to 5%. The specific method of continuous grading is: 0.075mm to 0.15mm accounts for 9.6%, 0.15mm to 0.3mm accounts for 4.8%, 0.3mm to 0.6mm accounts for 28.2%, 0.6mm to 1.18mm accounts for 18.6%, 1.18mm to 2.36mm accounts for 18%, and 2.36mm to 4.75mm accounts for 20.8%.
[0035] In some embodiments, the recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence; the particle size is 4.75 mm to 19 mm, and it is mixed in a continuous grading manner, and the apparent density is 1980 kg / m 3 ~2180kg / m 3 , the crushing index is 10% to 17%, the water absorption rate is 4% to 11%, and the moisture content is 4% to 7%. The specific method of continuous grading is: 4.75mm to 9.5mm accounts for 17.4%, 9.5mm to 13.2mm accounts for 6.1%, 13.2mm to 16mm accounts for 23.3%, and 16mm to 19mm accounts for 53.2%.
[0036] In some embodiments, the particle size distribution of the phosphogypsum is below 0.3 mm, and the phosphogypsum is dried during use, with a drying temperature of 100°C to 104°C and a drying time of 20h to 28h. Phosphogypsum is a dark gray powdered solid, the main component of which is CaSO4·2H2O. The phosphogypsum material used is ordinary solid waste phosphogypsum, which is only dried before use. Compared with other pretreatment methods for phosphogypsum, such as water washing, calcination, grinding modification and other methods, the method of the present invention is more convenient, the cost is greatly reduced, and it is convenient for large-scale industrial production.
[0037] On the other hand, the present invention provides a method for preparing a fatigue-resistant phosphogypsum recycled aggregate water-stable base material, comprising the following steps:
[0038] S1. Weigh each component according to mass percentage.
[0039] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0040] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0041] The present invention can realize the recycling and reuse of solid wastes such as phosphogypsum and waste concrete materials, and effectively ensure that the prepared water-stable base material has excellent fatigue resistance, and has important economic and promotion value.
[0042] The following is further explained through specific implementation.
[0043] Example 1
[0044] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing PU emulsion, EVA emulsion and SBR emulsion in a mass ratio of 1:0.2:2. The solid content of the PU emulsion is 40% and the pH value is 6.0. The solid content of the EVA emulsion is 40% and the pH value is 6.0. The solid content of the SBR emulsion is 40% and the pH value is 6.0.
[0045] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0046] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0047] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0048] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0049] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0050] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0051] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0052] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0053] Example 2
[0054] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing PU emulsion, EVA emulsion and SBR emulsion in a mass ratio of 1:0.4:1.8. The solid content of the PU emulsion is 40% and the pH value is 6.0. The solid content of the EVA emulsion is 40% and the pH value is 6.0. The solid content of the SBR emulsion is 40% and the pH value is 6.0.
[0055] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0056] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0057] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0058] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0059] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0060] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0061] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0062] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0063] Example 3
[0064] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing PU emulsion, EVA emulsion and SBR emulsion in a mass ratio of 1:0.6:1.6. The solid content of the PU emulsion is 40% and the pH value is 6.0. The solid content of the EVA emulsion is 40% and the pH value is 6.0. The solid content of the SBR emulsion is 40% and the pH value is 6.0.
[0065] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0066] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0067] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0068] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0069] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0070] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0071] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0072] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0073] Example 4
[0074] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing PU emulsion, EVA emulsion and SBR emulsion in a mass ratio of 1:0.8:1.4. The solid content of the PU emulsion is 40%, and the pH value is 6.0. The solid content of the EVA emulsion is 40%, and the pH value is 6.0. The solid content of the SBR emulsion is 40%, and the pH value is 6.0.
[0075] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0076] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0077] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0078] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0079] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0080] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0081] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0082] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0083] Example 5
[0084] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing PU emulsion, EVA emulsion and SBR emulsion in a mass ratio of 1:1:1. The solid content of the PU emulsion is 40% and the pH value is 6.0. The solid content of the EVA emulsion is 40% and the pH value is 6.0. The solid content of the SBR emulsion is 40% and the pH value is 6.0.
[0085] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0086] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0087] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0088] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0089] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0090] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0091] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0092] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0093] Example 6
[0094] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:6.8:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing PU emulsion, EVA emulsion and SBR emulsion in a mass ratio of 1:1.5:4.5. The solid content of the PU emulsion is 40% and the pH value is 6.0. The solid content of the EVA emulsion is 40% and the pH value is 6.0. The solid content of the SBR emulsion is 40% and the pH value is 6.0.
[0095] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0096] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0097] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0098] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0099] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0100] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0101] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0102] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0103] Example 7
[0104] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.8:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing PU emulsion, EVA emulsion and SBR emulsion in a mass ratio of 0.8:1:2. The solid content of the PU emulsion is 40% and the pH value is 6.0. The solid content of the EVA emulsion is 40% and the pH value is 6.0. The solid content of the SBR emulsion is 40% and the pH value is 6.0.
[0105] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0106] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0107] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0108] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0109] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0110] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0111] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0112] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0113] Comparative Example 1
[0114] A fatigue-resistant phosphogypsum recycled aggregate water-stabilized base material, which is prepared from a consolidation combination, a solid alkali activator, a PU emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and the water is 100:2.5:3.2:6.54, and the consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, and a total of 100%; the solid content of the PU emulsion is 40%, and the pH value is 6.0.
[0115] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0116] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0117] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0118] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0119] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0120] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% PU emulsion and 6.54% water by mass percentage.
[0121] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the composite polymer emulsion and water to form a mixture B; evenly mix the cement-based material, the solid alkali activator and the phosphogypsum to form a mixture C.
[0122] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0123] Comparative Example 2
[0124] A fatigue-resistant phosphogypsum recycled aggregate water-stable base material, which is prepared from a consolidation combination, a solid alkali activator, an SBR emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54, and the consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, and a total of 100%; the solid content of the SBR emulsion is 40%, and the pH value is 6.0.
[0125] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0126] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0127] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0128] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0129] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0130] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% SBR emulsion and 6.54% water by mass percentage.
[0131] S2. S2. Mix the recycled coarse aggregate and the recycled fine aggregate evenly to form a mixture A. Mix the composite polymer emulsion and water evenly to form a mixture B. Mix the cement-based material, the solid alkali activator and the phosphogypsum evenly to form a mixture C.
[0132] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0133] Comparative Example 3
[0134] A fatigue-resistant phosphogypsum recycled aggregate water-stable base material, which is prepared from a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54, and the consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total; the composite polymer emulsion is obtained by mixing a PU emulsion and an SBR emulsion in a mass ratio of 1:1; the solid content of the PU emulsion is 40%, and the pH value is 6.0; the solid content of the SBR emulsion is 40%, and the pH value is 6.0.
[0135] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0136] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0137] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0138] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0139] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0140] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0141] S2. S2. Mix the recycled coarse aggregate and the recycled fine aggregate evenly to form a mixture A. Mix the composite polymer emulsion and water evenly to form a mixture B. Mix the cement-based material, the solid alkali activator and the phosphogypsum evenly to form a mixture C.
[0142] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0143] Comparative Example 4
[0144] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing a PU emulsion and an EVA emulsion in a mass ratio of 1:1. The solid content of the PU emulsion is 40% and the pH value is 6.0. The solid content of the EVA emulsion is 40% and the pH value is 6.0.
[0145] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0146] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0147] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0148] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0149] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0150] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0151] S2. S2. Mix the recycled coarse aggregate and the recycled fine aggregate evenly to form a mixture A. Mix the composite polymer emulsion and water evenly to form a mixture B. Mix the cement-based material, the solid alkali activator and the phosphogypsum evenly to form a mixture C.
[0152] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0153] Comparative Example 5
[0154] The invention discloses an anti-fatigue phosphogypsum recycled aggregate water-stable base material. The water-stable base material is prepared by a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:2.5:3.2:6.54. The consolidation combination comprises the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, which is 100% in total. The composite polymer emulsion is obtained by mixing EVA emulsion and SBR emulsion in a mass ratio of 1:1. The solid content of the EVA emulsion is 40% and the pH value is 6.0. The solid content of the SBR emulsion is 40% and the pH value is 6.0.
[0155] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0156] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0157] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3, water absorption is 5.5% and moisture content is 4.7%.
[0158] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0159] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0160] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator, 3.2% composite polymer emulsion and 6.54% water by mass percentage.
[0161] S2. S2. Mix the recycled coarse aggregate and the recycled fine aggregate evenly to form a mixture A. Mix the composite polymer emulsion and water evenly to form a mixture B. Mix the cement-based material, the solid alkali activator and the phosphogypsum evenly to form a mixture C.
[0162] S3. Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stable base material.
[0163] Comparative Example 6
[0164] A fatigue-resistant phosphogypsum recycled aggregate water-stabilized base material, which is prepared from a consolidation combination, a solid alkali activator and water, wherein the mass ratio of the consolidation combination, the solid alkali activator and water is 100:2.5:6.54, and the consolidation combination consists of the following raw materials in mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, and a total of 100%.
[0165] The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 3:25.
[0166] Phosphogypsum is a dark grey powdery solid with a particle size distribution of less than 0.3 mm. Phosphogypsum is dried at 100°C for 24 hours before use.
[0167] The recycled fine aggregate is obtained by crushing and screening waste concrete materials. It is mixed in a continuous grading manner with 0.075mm-0.15mm accounting for 9.6%, 0.15mm-0.3mm accounting for 4.8%, 0.3mm-0.6mm accounting for 28.2%, 0.6mm-1.18mm accounting for 18.6%, 1.18mm-2.36mm accounting for 18%, and 2.36mm-4.75mm accounting for 20.8%, and the apparent density is 2017kg / m 3 , water absorption is 5.5% and moisture content is 4.7%.
[0168] The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence. It is mixed in a continuous grading manner with 4.75mm-9.5mm accounting for 17.4%, 9.5mm-13.2mm accounting for 6.1%, 13.2mm-16mm accounting for 23.3%, and 16mm-19mm accounting for 53.2%, and the apparent density is 2113kg / m 3 , the crushing index is 14%, the water absorption rate is 5.8%, and the moisture content is 4.3%.
[0169] The preparation method of fatigue-resistant phosphogypsum recycled aggregate water-stable base material comprises the following steps:
[0170] S1. Weigh the components of the consolidation combination by mass percentage: 5% cement, 20% phosphogypsum, 30% recycled fine aggregate, 45% recycled coarse aggregate, totaling 100%; based on the mass of the consolidation combination of 100%, weigh 2.5% solid alkali activator and 6.54% water by mass percentage.
[0171] S2. Evenly mix the recycled coarse aggregate and the recycled fine aggregate to form a mixture A; evenly mix the cement-based material, the solid alkali activator, the phosphogypsum and water to form a mixture C.
[0172] S3. Add mixture C into mixture A, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stabilized base material.
[0173] The following performance tests were performed on the road base materials obtained in Examples 1 to 7 and Comparative Examples 1 to 6. The results are shown in Tables 1 to 3.
[0174] 1. Fatigue performance test
[0175] The stress control method is adopted, the applied load is a continuous Havesine wave, and the load standard frequency is 10 Hz. The maximum stress Pmax in each example is the same, and the splitting strength of 0.9 times and 0.7 times of that of comparative example 6 is selected, that is, 171 kPa and 133 kPa, and Pmin is selected as 0. Fatigue improvement degree γ = [(N i-N0) / N0]×100%, wherein N0 is the maximum fatigue times of the group of comparative example 6. In Examples 1 to 7, i=1, 2, 3, 4, 5, 6, 7. In Comparative Examples 1 to 5, i=D1, D2, D3, D4, D5.
[0176] 2. Unconfined compressive strength test
[0177] According to the requirements of the Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering (JTG E51-2009), the mixed materials are made into standard test pieces of φ100mm×h100mm, with a compaction degree ≥98%, and placed in a standard curing room (20℃±2, humidity>95%) for curing to the required age; on the last day of the curing period, the specimens are taken out, immersed in water at 20℃±2 for 24 hours, taken out and dried with a soft cloth, and then an unconfined compressive strength test is carried out, with a loading rate of 1mm / min, six parallel samples, and the representative value is taken.
[0178] Table 1 0.9 times fatigue performance of base material
[0179]
[0180]
[0181] Table 1 is a fatigue performance table of the base materials of Examples 1 to 7 and Comparative Examples 1 to 6 under 0.9 times fatigue load. The greater the maximum fatigue times, the better the fatigue resistance. It can be seen from Table 1 that due to the high fatigue load of 0.9 times, only the maximum fatigue times of Examples 1 to 3 reach more than 10,000 times. In Examples 1 to 4, the total amount of three emulsions added is a fixed value, the proportion of PU emulsion and EVA emulsion increases, and the proportion of SBR emulsion continues to decrease. It can be seen from Table 1 that the maximum fatigue times of Examples 1 to 4 continue to decrease. This shows that the increase in the proportion of PU emulsion and EVA emulsion improves the rigidity of this composite material, and the continuous decrease in the proportion of SBR emulsion reduces the toughness and fatigue resistance of this composite material. Compared with Example 4, the EVA emulsion in Example 5 increased by 25%, the SBR emulsion decreased by 28.6% compared with the SBR emulsion in Example 4, and the PU emulsion remained unchanged. The maximum fatigue times of Example 5 decreased, which shows that the increase of EVA emulsion accompanied by the decrease of SBR emulsion is not conducive to the fatigue resistance of this composite material. Compared with Example 4, the EVA emulsion in Example 6 increased by 87.5%, the SBR emulsion increased by 221.4%, the PU emulsion remained unchanged, and the maximum fatigue times in Example 6 decreased compared with Example 4. This shows that the increase of EVA emulsion and SBR emulsion is not conducive to the anti-fatigue performance of this composite material. In Example 7, the PU emulsion decreased by 20% compared with Example 5, the SBR emulsion increased by 100% compared with Example 5, the EVA emulsion remained unchanged, and the maximum fatigue times in Example 7 increased compared with Example 5, which shows that the PU emulsion mainly plays a role in enhancing the rigidity of this material, and the SBR emulsion mainly plays a role in enhancing the elasticity and anti-fatigue of this material.
[0182] In the comparative examples, comparative example 6 does not contain emulsion, and the maximum fatigue number of comparative example 6 is the lowest. This shows that the reasonable incorporation of PU emulsion, EVA emulsion and SBR emulsion can enhance the anti-fatigue performance of this composite material. Comparative example 1 and comparative example 2 are both only mixed with one emulsion, namely PU emulsion and SBR emulsion, and the amount of incorporation is consistent with the total amount of emulsions in Example 1-Example 4. However, comparative example 1 and comparative example 2 only improve the anti-fatigue performance by 17% and 25.1% relative to comparative example 6. This shows that only the incorporation of PU emulsion and SBR emulsion alone will improve the anti-fatigue performance of this composite material, but the improvement effect is small. In comparative examples 3 to comparative examples 5, the two emulsions are mixed in a one-to-one ratio, and the total amount of incorporation is the same. Comparative example 3 is a one-to-one mixing of PU emulsion and SBR emulsion, comparative example 4 is a one-to-one mixing of PU emulsion and EVA emulsion, and comparative example 5 is a one-to-one mixing of EVA emulsion and SBR emulsion. It can be seen that the maximum fatigue times of Comparative Examples 3 and 5 are both higher than those of Comparative Example 4, which indicates that when the two emulsions are compounded in a one-to-one ratio, the anti-fatigue performance of the test group containing the SBR emulsion is higher than that of the test group not containing the SBR emulsion. At the same time, it is found that the anti-fatigue performance of Comparative Example 5 is higher than that of Comparative Example 3, which indicates that the PU emulsion shows an increase in rigidity and a decrease in elasticity of the composite material compared to the EVA emulsion.
[0183] Table 2 0.7 times fatigue performance of base material
[0184]
[0185]
[0186] Table 2 is a fatigue performance table of the base materials of Examples 1 to 7 and Comparative Examples 1 to 6 under 0.7 times fatigue load. The greater the maximum fatigue times, the better the fatigue resistance. It can be seen from Table 2 that since 0.7 times fatigue load is lower than 0.9 times fatigue load, it can be seen from Table 1 to Table 2 that the maximum fatigue times of all embodiments and comparative examples in Table 2 are more than 10,000 times. The maximum fatigue times of the embodiments are the same as those in Table 1, and the principle is the same as that in Table 1. The maximum fatigue times of the comparative test group are the same as those in Table 1, and the principle is the same as that in Table 1.
[0187] Table 3 Compressive strength properties of base materials
[0188]
[0189] Table 3 is a table of 7d and 28d unconfined compressive strength of the base materials of Examples 1-7 and Comparative Examples 1-6. It can be seen from Examples 1 to 4 in Table 3 that the 7d and 28d unconfined compressive strengths continue to increase. In Examples 1 to 4, the total amount of the three emulsions added is a fixed value, the proportion of PU emulsion and EVA emulsion increases, and the proportion of SBR emulsion decreases, which has an enhancing effect on strength. It shows that the combination of PU emulsion and EVA emulsion has an enhancing effect on strength in this composite material, and as the proportion of these two emulsions increases, the strength of the composite material increases. It can be seen from Example 5 that the EVA emulsion in the mixed emulsion of Example 5 is compared with Example 4. The EVA emulsion increased by 25%, the SBR emulsion decreased by 28.6%, and the PU emulsion remained unchanged. The 7d and 28d unconfined compressive strengths of Example 5 increased compared with Example 4, which shows that the PU emulsion remains unchanged in this composite material. Increasing the EVA emulsion content alone while reducing the SBR emulsion content can also increase the strength of this material. It can be seen from Example 6 that the EVA emulsion in the mixed emulsion of Example 6 increased by 50% compared with the EVA emulsion in Example 5, the SBR emulsion increased by 350% compared with the SBR emulsion in Example 5, and the PU emulsion remained unchanged. The 7d and 28d unconfined compressive strengths of Example 6 decreased compared with Example 5, which shows that when the increase of SBR emulsion in this composite material is much greater than that of EVA emulsion, the strength will be reduced. It can be seen from Example 7 that the PU emulsion in Example 7 decreased by 20% compared with Example 5, and the SBR emulsion increased by 100% compared with Example 5. The 7d and 28d unconfined compressive strengths of Example 7 decreased compared with Example 5, which shows that the SBR emulsion in this composite material increased significantly, and the strength of the composite material was also reduced with the reduction of PU emulsion.
[0190] In the comparative examples, comparative example 6 does not contain emulsion. It can be seen that the 7d and 28d unconfined compressive strengths of comparative example 6 are the lowest, which shows that the reasonable addition of PU emulsion, EVA emulsion and SBR emulsion can enhance the strength of this composite material. Comparative examples 1 and 2 are both mixed with only one emulsion, namely PU emulsion and SBR emulsion, and the amount added is consistent with the total amount of emulsions in Examples 1 to 4. The 7d and 28d unconfined compressive strengths of comparative example 1 are the highest among all test groups, which shows that the use of PU emulsion alone has a significant reinforcing effect on this composite material. The 7d and 28d unconfined compressive strengths of comparative example 2 are only higher than the strength of comparative example 6, which shows that the use of SBR emulsion alone has a smaller reinforcing effect on this composite material. In comparative examples 3-5, the two emulsions are mixed in a one-to-one ratio, and the total amount added is the same. Comparative Example 3 is a mixture of PU emulsion and SBR emulsion in a ratio of 1:1, Comparative Example 4 is a mixture of PU emulsion and EVA emulsion in a ratio of 1:1, and Comparative Example 5 is a mixture of EVA emulsion and SBR emulsion in a ratio of 1:1. The 7d and 28d unconfined compressive strengths are Comparative Example 4, Comparative Example 3, and Comparative Example 5, respectively. This shows that the mixture of PU emulsion and EVA emulsion in a ratio of 1:1 can play a better reinforcing role, and the weakest reinforcing effect is the mixture of EVA emulsion and SBR emulsion in a ratio of 1:1.
[0191] From Tables 1 to 3, it can be seen that the 7d unconfined compressive strength of Examples 1 to 7 and Comparative Examples 1 to 6 are all above 3MPa, specifically in the range of 3.02MPa to 4.28MPa, meeting the minimum strength (3MPa) requirement for base materials of highways and first-class highways with medium and light traffic intensities in the "Technical Specifications for Construction of Highway Pavement Base (JTG / T F20-2015)". Among them, the 7d unconfined compressive strength of Example 1 is 3.38MPa, which is 21% lower than the 7d unconfined compressive strength (4.28MPa) of Comparative Example 1, but the fatigue resistance times of Example 1 under two loads are the largest, much higher than that of Comparative Example 1. Overall, the mix ratio of Example 1 is selected as the optimal fatigue resistance mix ratio.
[0192] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention only describes the preferred embodiments. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0193] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A fatigue-resistant phosphogypsum recycled aggregate water-stable base material, characterized in that: The water-stabilized base material is prepared from a consolidation combination, a solid alkali activator, a composite polymer emulsion and water, wherein the mass ratio of the consolidation combination, the solid alkali activator, the composite polymer emulsion and water is 100:1-3:2-6:5-8, and the consolidation combination is composed of the following raw materials in mass percentage: 4%-6% of cement-based materials, 17%-22% of phosphogypsum, 28%-31% of recycled fine aggregate, 44%-48% of recycled coarse aggregate, and the total is 100%; the composite polymer emulsion is obtained by mixing EVA emulsion, SBR emulsion and PU emulsion in a mass ratio of 0.10-1.6:1-5.5:0.8-3.
2.
2. The fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to claim 1, characterized in that: The composite polymer emulsion is obtained by mixing EVA emulsion, SBR emulsion and PU emulsion according to a mass ratio of 0.2-1.6:1-4.5:0.8-3.
2.
3. The fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to claim 1, characterized in that: The mass ratio of the solidified combination to the composite polymer latex is 100:2.2-3.
5.
4. The fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to claim 1, characterized in that: The solid alkali activator is obtained by mixing sodium hydroxide and sodium silicate in a mass ratio of 1:3.2-8.
8.
5. The fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to claim 1, characterized in that: The cement-based material is cement or a mixture of cement and mineral admixtures, wherein the mineral admixture is at least one of waste steel slag, fly ash, slag and stone powder.
6. The fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to claim 1, characterized in that: The recycled fine aggregate is obtained by crushing and screening waste concrete materials; the particle size is 0.075mm-4.75mm, and the apparent density is 1960kg / m 3 ~2100kg / m 3 The water absorption rate is 4% to 8%, and the moisture content is 2% to 5%.
7. The fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to claim 1, characterized in that: The recycled coarse aggregate is obtained by sorting, crushing and screening construction waste in sequence; the particle size is 4.75mm-19mm, and the apparent density is 1980kg / m 3 ~2180kg / m 3 The crushing index is 10% to 17%, the water absorption rate is 4% to 11%, and the moisture content is 4% to 7%.
8. The fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to claim 1, characterized in that: The particle size distribution of the phosphogypsum is below 0.3 mm. The phosphogypsum is dried during use at a drying temperature of 100° C. to 104° C. and a drying time of 20 h to 28 h.
9. The fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to claim 2, characterized in that: The solid content of the EVA emulsion is 35% to 55%, and the pH value is 6.0 to 7.0; the solid content of the SBR emulsion is 35% to 55%, and the pH value is 7.0 to 8.0; the solid content of the PU emulsion is 35% to 55%, and the pH value is 7.0 to 9.
0.
10. A method for preparing the fatigue-resistant phosphogypsum recycled aggregate water-stable base material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh each component according to mass percentage; The recycled coarse aggregate and the recycled fine aggregate are mixed evenly to form a mixture A; the composite polymer emulsion and water are mixed evenly to form a mixture B; the cement-based material, the solid alkali activator and the phosphogypsum are mixed evenly to form a mixture C; Add mixture C and mixture B into mixture A in sequence, and stir evenly to obtain fatigue-resistant phosphogypsum recycled aggregate water-stabilized base material.
Citation Information
Patent Citations
Pavement base material based on organic-inorganic cementing material synergistically stabilized phosphogypsum and recycled aggregate and preparation method of pavement base material
CN116283118A